2014
DOI: 10.1093/annhyg/meu049
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols and Criteria Gases in an Underground Mine That Uses FAME Biodiesel Blends

Abstract: The contribution of heavy-duty haulage trucks to the concentrations of aerosols and criteria gases in underground mine air and the physical properties of those aerosols were assessed for three fuel blends made with fatty acid methyl esters biodiesel and petroleum-based ultra-low-sulfur diesel (ULSD). The contributions of blends with 20, 50, and 57% of biodiesel as well as neat ULSD were assessed using a 30-ton truck operated over a simulated production cycle in an isolated zone of an operating underground meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The effects of FAME bio-diesel on NO X emissions appear to depend on a number of parameters, including engine technology, certification level (Durbin et al, 2007; Hoekman and Robins, 2012), and engine operating conditions (Muller, Boehman and Martin, 2014). The aerosols emitted by engines operated on FAME biodiesel fuels were found to be characterized by smaller median diameters than the corresponding size distributions observed for the ULSD (Bugarski et al, 2010; Bugarski et al, 2014). The formation of higher number concentrations in nucleation mode aerosols relative to ULSD were reported by Schönborn et al (2009) for several types of FAME bio-diesels.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…The effects of FAME bio-diesel on NO X emissions appear to depend on a number of parameters, including engine technology, certification level (Durbin et al, 2007; Hoekman and Robins, 2012), and engine operating conditions (Muller, Boehman and Martin, 2014). The aerosols emitted by engines operated on FAME biodiesel fuels were found to be characterized by smaller median diameters than the corresponding size distributions observed for the ULSD (Bugarski et al, 2010; Bugarski et al, 2014). The formation of higher number concentrations in nucleation mode aerosols relative to ULSD were reported by Schönborn et al (2009) for several types of FAME bio-diesels.…”
Section: Introductionmentioning
confidence: 69%
“…Schönborn et al (2009) found that concentrations of nucleation mode aerosols were highest for the long-chained, fully saturated FAMEs. It is important to note that the formation of nucleation mode aerosols is strongly affected by dilution and environmental conditions, and that increase in nucleation particles was not observed in the studies conducted in underground environments where soybean oil-derived FAME biodiesels were used (Bugarski et al, 2010; Bugarski et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations